If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(y + -7) = 2y + -38 Reorder the terms: -6(-7 + y) = 2y + -38 (-7 * -6 + y * -6) = 2y + -38 (42 + -6y) = 2y + -38 Reorder the terms: 42 + -6y = -38 + 2y Solving 42 + -6y = -38 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 42 + -6y + -2y = -38 + 2y + -2y Combine like terms: -6y + -2y = -8y 42 + -8y = -38 + 2y + -2y Combine like terms: 2y + -2y = 0 42 + -8y = -38 + 0 42 + -8y = -38 Add '-42' to each side of the equation. 42 + -42 + -8y = -38 + -42 Combine like terms: 42 + -42 = 0 0 + -8y = -38 + -42 -8y = -38 + -42 Combine like terms: -38 + -42 = -80 -8y = -80 Divide each side by '-8'. y = 10 Simplifying y = 10
| (3a+5)=2a-7 | | (3a+5)=-(2a-7) | | 7y=6y+-4.7 | | 3-n/3=n/6-8 | | 7a+5-4=x | | -7(t+1)=28 | | 9-4b-10=x | | -13-(-20)=x/4 | | 11-10x=44-17 | | -8n-10+n-6=x | | 40=9t-14t | | -31-9x=7x+1 | | 5+9x+x+1=x | | 8x-22=4x+22 | | 5x+8=132-9x | | 2y+7=y-1 | | 5(x+6)-5= | | 8x-11-9x+4=-5x+23 | | (3a+5)=2a+7 | | -5-4x=10x-9 | | 4(m+5)= | | a/5+2/5=-2+a | | 580=55c+250 | | -[2p+(-3p+6)]-[-(-5p+(3+10p))-6p]= | | 14m-3= | | 12w^2-2w+64=0 | | w/-8=-1/2 | | 12w^2-2w+6=0 | | 6m+5m+3m-3= | | -58+17=-41 | | -58+17= | | 2(x-4)-3(x-5)=-7 |